Sacred to Safe Pilgrimages: What’s Next in Vaccination? - Syed Omar, Sharifah Faridah (International Journal of Human and Health Sciences (IJHHS), 2024)
Vaccination is an effective preventive measure that has been used in Hajj pilgrimage settings to control the transmission of infectious diseases. People who travel to areas where meningococcal disease is more common, or who travel to mass gatherings, are recommended to receive MenACWY vaccines. This lecture will highlight the guidelines and importance of meningococcal and flu vaccination amongst pilgrims as they travel to the Kingdom of Saudi Arabia to fulfil their Hajj and Umrah pilgrimages. Dr. Sharifah will also be sharing the latest clinical data of meningococcal A, C, W, Y vaccine. International Journal of Human and Health Sciences Supplementary Issue 01: 2024 Page: S11